Stolen - Christopher, Lucy (Chicken House, 2010)
Sixteen-year-old Gemma, a British city-dweller, is abducted while on vacation with her parents and taken to the Australian outback, where she soon realizes that escape attempts are futile, and in time she learns that her captor is not as despicable as she first believed.